MEMBANGUN GENERASI BERAKHLAK MULIA: BAKTI SOSIAL STIE GANESHA DALAM RANGKA PERINGATAN ISRA MI'RAJ NABI MUHAMMAD SAW - Kohar, Abdul; Tohiroh, Tohiroh; Saksana, Joned Ceilendra; Murtini, Sri; Prajogo, Budi; Siregar, Fuad; Pardian, Ramadani; Ruvi, Muhammad; Lesmana, Asep Surya; Candra, Hendra; Abas, Farhat; Saefullah, Aep; Putera, Alifi Restu; Salima, Rianti; Muharifah, Isnaini; Nurhayati, Nurhayati (Gapenas Publisher, 2025)
This activity aims to instill noble moral values exemplified by the Prophet Muhammad to the community, as well as increase social care through social services. This program involved participants from representatives of majelis taklim throughout the Pisangan sub-district. Pisangan with a target beneficiary of 1,000 coupons containing basic necessities and other basic needs. Community service activities were carried out on Sunday, January 5 and 12, 2025, at the STIE Ganesha Campus and the Baiturrahman mosque, Pisangan Village. The activity implementation method consists of three main stages: (1) Isra Mi'raj Commemoration which is filled with tausiyah about the morals of the Prophet Muhammad, (2) Distribution of food and drink to the community. morals of the Prophet Muhammad, (2) Distribution of Social Service Coupons, and (3) Distribution of Assistance to People in Need. This activity successfully reached around 250 participants representing mosques and taklim assemblies. Through this program, the community is expected to take lessons from the Prophet's struggle and apply them in everyday life by strengthening solidarity and social care. The results of the activity showed the enthusiasm of the community in participating in the event and positive acceptance of the assistance provided. The implications of this activity are expected to encourage the community to be more active in religious and social activities, as well as strengthen the relationship between STIE Ganesha and the community. between STIE Ganesha and the local community. This activity also reinforces character education values based on noble morals that are relevant for young generation